MANAGING THE ELECTRONIC ADVERTISEMENTS AND ITS ROLE IN RAISING THE E-MARKETING LEVEL (World Bulletin of Social Sciences, 2022)
A major role of managing advertisements is the success of advertising marketing, as it identifies advertising goals and these goals have to respond with decisions that related to the identified market and putting the trade mark. The advertisements are a major and significant detail of the media policy that have to be adopted by the administration to communicate the idea of the advertisement and showing the strength points. Advertising is one of the most significant elements of the promotional mix, and its significance reveals with the different fields of goods marketing, ideas, services and people, due to its significant influences on consumer behaviors at the present time and future. In view of the increase of interest in electronic advertising activities in the recent period, due to the multitude of its means, techniques and methods, as it took a big share of advertisements around the world, because of its ease and speed of access to customers with many advantages that differentiate it from regular advertising. Nowadays, electronic advertising has become a global business led by large professional corporations in the field of management and through which, they earn very large profits.
Keywords: Electronic Advertisements; Managing Advertisements; Electronic Marketing